Enhancing Kenya Agricultural Observatory Platform (KAOP) by integrating AICCRA’s AgDataHub - Akshatha, Annaiah; Dhulipala, Ram (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Kenya Climate Smart Agriculture Project (KCSAP), through the Kenya Agricultural and Livestock Research Organization (KALRO) and Kenya Meteorological Department (KMD)3 launched a digital platform called Kenya Agricultural Observatory Platform (KAOP) in 2018. The KAOP offered users and farmers access to market intelligence, 16-day weather forecasts and good agricultural practises (GAP). Though this information was useful, the platform lacked climatological data, satellite imagery data as well as data from other publicly available sources. The AgDataHub designed and developed under AICCRA Kenya was able to aggregate these datasets from different sources and integrate this seamless into the KAOP platform and enhancing its datasets and functionalities. The KAOP with AgDataHub referred to as the "new KAOP", will offer advanced data resources, enabling users to generate actionable CIS for practical applications. Integration with AgDataHub has boosted KAOP’s functionality and user experience by providing better access to weather forecasts and market information, enhancing its value for farmers and stakeholders. Below is a brief description of the new information that is now available on KAOP.